2022
DOI: 10.5812/zjrms-112107
|View full text |Cite
|
Sign up to set email alerts
|

Snakebites on Distal Extremities; Three Years of Experiences

Abstract: Background: Globally, 1.5 to 3 million people are exposed to snakebites each year. More than 100,000 of these cases, primarily in the tropics, result in death. This study includes an analysis of a university hospital's three-year experiences of distal extremity snakebites. Methods: This study includes 68 patients presented at the Emergency Department (ED) of Gaziantep University Hospital with snakebites on distal extremities (hands, fingers, and feet) between 01/03/2014 and 01/03/2017. Results: A total of 68 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The rich herpetofauna has more than ten venomous snake species, several of which with an unresolved taxonomic status 18,50,51 . Similar to tropical and subtropical regions, snakebite represents a major health burden in Türkiye, but the exact magnitude remains unclear due to the lack of comprehensive data [52][53][54] . Several studies address concrete numbers about snakebite envenoming in Türkiye, like Oto and Haspolat (2021) showed that in southeast regions alone 108 children has been hospitalized between 2006 and 2011, not including dry bites 55 .…”
Section: Introductionmentioning
confidence: 99%
“…The rich herpetofauna has more than ten venomous snake species, several of which with an unresolved taxonomic status 18,50,51 . Similar to tropical and subtropical regions, snakebite represents a major health burden in Türkiye, but the exact magnitude remains unclear due to the lack of comprehensive data [52][53][54] . Several studies address concrete numbers about snakebite envenoming in Türkiye, like Oto and Haspolat (2021) showed that in southeast regions alone 108 children has been hospitalized between 2006 and 2011, not including dry bites 55 .…”
Section: Introductionmentioning
confidence: 99%
“…On the border between Europe and Asia, Türkiye represents a hotspot of snake diversity, hosting members of all four Palearctic viper genera. ,− Similar to tropical and subtropical regions, snakebite represents a major health burden in Türkiye, but the exact magnitude remains unclear due to the lack of comprehensive data. Only a few studies address concrete numbers about snakebite envenoming in Türkiye. ,, While awareness of snakebite grows, the species responsible for a bite are often not known. It is therefore necessary to investigate the range of venomous snakes in the country and the extent to which their venoms are composed.…”
Section: Introductionmentioning
confidence: 99%